Badik in Logic and Legal Meaning - Kadriah, Ayyub; Sumarna, Dadang (Intellectual Law Review (ILRE), 2023)
The badik, the traditional weapon of the Bugis and Makassarese, is not just a physical tool, but a symbol rich with social and cultural meaning. The function of the badik goes beyond its role as a defence tool; it is a 'text' in the Bugis and Makassarese cultural sign system that mediates social and legal relations. Social status, valour, or certain obligations in society can be signalled by the type of badik one possesses. The badik also carries important cultural values such as siri' the concept of shame or self-respect and ati macinnong meaning a clear heart, which govern its use in contexts such as fighting, traditional ceremonies, or conflict resolution. In addition, the use of the badik should be based on logical reasoning to avoid further misuse or damage. The analysis of the badik therefore focuses not only on its physical aspects but also involves an in-depth understanding of its legal norms as well as its symbolic and anthropological meanings.